(untitled) (Journal of Contemporary Issues in Accounting, 2022)
The main objective of the study is to ascertain the relationship between customers’ loyalty and sales performance of Dangote Cement in Awka, Anambra State. The study specifically examines the relationship between emotional loyalty and consumer purchase intention; and, secondly the relationship between behavioural loyalty and consumer purchase intention. The study adopts the survey research design. The sample comprised of one hundred and sixty five (165) consumers of Dangote cement in Awka. The study relied on primary data; obtained from a structured questionnaire administered to the consumers. The data were analysed using descriptive statistics and the hypotheses tested using Pearson correlation coefficient. The results showed a positive significant relationship between emotional loyalty and consumer purchase intention; and, secondly a positive significant relationship between behavioural loyalty and consumer purchase intention. Based on this the study recommends that manufacturing companies strive to maintain customer trust via quality product or service delivery. The use of loyalty programs as strategies for rewarding customers is further encouraged; lastly, manufacturing companies are advised to engage in periodic customer satisfaction survey.